Delayed-Type Hypersensitivity and Immunity Against Aerogenic Tuberculosis in Guinea Pigs - Reggiardo, Zulema (1974)
In experiments described herein, it was observed that guinea pigs with delayed-type hypersensitivity to tuberculoproteins under various experimental conditions, with or without passive transfer of serum from immune donors, manifested no acquired immunity against aerogenically induced tuberculosis. These results are discussed in relation to the previous observations of other investigators and to the general problem of cellular hypersensitivity and immunity against facultative intracellular bacteria.